Literature review: current trends and developments in employee recruitment - Triastuti, Sefina (Jurnal Ilmiah WUNY, 2025)
Recruitment and employee selection have experienced rapid development with technological advances significantly transforming the process. However, many companies still employ traditional methods that present challenges including lengthy time requ irements, higher costs, and potential bias. This study examines trends and recent developments in employee recruitment processes through systematic literature review. This research employs literature review methodology using secondary data from journals, research reports, and industry publications. Literature was selected based on relevance, quality, and recency, focusing on publications from the last five years using academic databases such as Jurnal Sinta, Google Scholar, JSTOR, and ScienceDirect.Current recruitment trends show significant shift toward digital technology use throughout the process. Online platforms, artificial intelligence (AI), and applicant tracking systems (ATS) have become integral in expanding candidate reach, accelerating recruitment, and enhancing candidate experience. Technology enables companies to screen candidates more efficiently, reduce costs, and improve selection accuracy compared to traditional methods. Latest trends emphasize the importance of diversity, inclusivity, and social responsibility in recruitment processes, becoming increasingly relevant amid social changes and millennial generation expectations.